Identifikasi Prioritas Masalah Unit Rekam Medis di Puskesmas Nusukan - Puguh Ika Listyorini (Poltekkes Kemenkes Semarang, 2020)
Health services consist of two kinds, namely medical and non-medical services. One of the non-medical services provided by the medical record unit. In providing medical record unit services do not always run well, therefore it is necessary to identify the priority determination of the problem to find out what problems must be solved first. The Multiple Criteria Utility Assessment (MCUA) method is a method of determining priority problems with scoring techniques. The purpose of this study was to determine the priority of problems in the medical record unit of the Nusukan Health Center using the MCUA Method. This research uses descriptive research design with 4 speakers. According to the results of the identification of problems carried out by the Group Group Discussion (FGD) that there are 3 problems in the medical record unit of the Nusukan Public Health Center, namely the lack of resources for medical records, medical record documents, and the availability of rooms for managing medical records that are still limited. The priority problem with the MCUA method shows that the problem with the highest value is the lack of medical record personnel. Before making additional workforce, it is recommended to calculate the workforce needs in the medical record unit according to the workload of the medical record officer so that the additional workforce is in accordance with the workload of the officer.AbstrakPelayanan kesehatan terdiri dari dua macam yaitu pelayanan medis dan non medis. Pelayanan non medis salah satunya diberikan oleh unit rekam medis. Dalam memberikan pelayanan unit rekam medis tidak selalu berjalan dengan baik, oleh karena itu perlu dilakukan identifikasi penentuan prioritas masalah untuk mengetahui masalah apa saja yang harus diselesaikan terlebih dahulu. Metode Multiple Criteria Utility Assessment (MCUA) adalah salah satu metode penentuan prioritas masalah dengan tekhnik scoring. Tujuan penelitian ini untuk mengetahui prioritas masalah di unit rekam medis Puskesmas Nusukan menggunakan Metode MCUA. Penelitian ini menggunakan desain penelitian deskriptif dengan 4 orang narasumber. Menurut hasil identifikasi masalah yang dilakukan dengan Forum Group Discussion (FGD) bahwa terdapat 3 masalah di unit rekam medis Puskesmas Nusukan, yaitu kurangnya sumber daya tenaga rekam medis, missfile dokumen rekam medis, dan ketersediaan ruagan untuk penggelolaan rekam medis yang masih terbatas. Prioritas masalah dengan metode MCUA menunjukkan masalah dengan nilai paling tinggi adalah kurangnya sumber daya tenaga rekam medis. Sebelum melakukan penambahan tenaga kerja, maka disarankan agar menghitung kebutuhan tenaga kerja di unit rekam medis menurut beban kerja petugas rekam medis agar penambahan tenaga kerja sesuai dengan beban kerja petugas.